Risk Analysis Characteristic, Socio- Economic, Behavior, and Environmental Factors of Malaria Incidence in Arongan Lambalek, West Aceh - Susy Sriwahyuni S; Rinidar Rinidar; Sugito Sugito (Jurnal Natural, 2015)
Malaria is  an infections disease of global concern, The subdistrict of Arongan lambalek in Aceh Barat district which belongs to the Medium Incidence Area category was a malaria endemic area with API with 3,67 at 1000  Population in 2013. The Annual Parasite Incidence was higher than National Parasite Malaria Incidence than is less API  1 at 1000 population. The aim of the study was to analyze the characteristic, socio-economic, behavioral, environmental factors to determine the influence of malaria incidence in Arongan lambalek sub district, Aceh Barat regency. This study was designed as case control or retrospective. As the case of the study, there were thirty-three (33) malaria positive people were involved. Laboratory test or rapid diagnostic test  was employed to select 33 respondents from malaria negative. Thus, make totally 66 respondents. The result of this study shows that there are five variables are risk factors for the incidence of malaria such as occupation (p-value =0,000, OR = 0,05), knowledge (p-value =0,000, OR =  17,5), attitude (p-value =0,001, OR = 7,43), action (p-value = 0,000, OR =  9,8) and  environment (p-value =  0,000, OR =  9,0). The result of multivariate analysis shows that knowledge is the risk factor with the most dominant influence on the incident of malaria (p = 0,006, OR=12,783, Confidence interval (CI) 95% =2,045– 79,893). Need for outreach to the community about malaria do this more often for more knowledge and and society information.